The controllable synthesis of Si/Ge composites with a synergistic effect for enhanced Li storage performance. Issue 7 (10th June 2019) - Ma, Kai; Lin, Ning
Abstract : Ge improves the electron and ion diffusion and mitigates the electrochemically induced mechanical degradation of Si electrodes. Abstract : Si is a promising anode material due to its high capacity and low potential; however, the inferior electron and ion diffusion and the large volume change hinder its commercial application. In this work, the simple ball-milling method is applied to incorporate Si with Ge to prepare nanostructured Si/Ge nanocomposites with the even distribution of flocculent Si and Ge particles, in which Ge improves the electron and ion diffusion and mitigates the electrochemically induced mechanical degradation of Si electrodes. When evaluated as anode materials, Si/Ge composites show superior electrochemical performance than the Si electrode. After optimizing the ratio and balancing capacity with cycling stability, the SG-4 (the molar ratio of Si : Ge = 4 : 1) composite delivers an initial charge capacity of 2040.3 mA h g −1 and the capacity of 1761 mA h g −1 is retained at 0.6 A g −1 after 150 cycles, with the corresponding capacity retention of 86.3%. Even at the high current density of 2 A g −1, the capacity fading rate is only 0.0596% per cycle after 500 cycles. Ex situ XRD demonstrates that the good performance is mainly attributed to the synergistic effects of Ge and Si. The full cell with SG-4 as the anode and LiCoO2 as the cathode delivers a capacity of 137.3 mA h g −1 after 50 cycles.